Factors Affecting Physical Activity Participation Among University Students - Oluyinka, Solomon; Endozo, Anatalia (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The Physical activities are indispensable to be healthy and away from illness, yet, students ignoring it. The factors affecting physical activity participation among university students in the Philippines examined in this study. Modified International Physical Activity Questionnaire adopted, Stata 13 and SPSS utilized to justify the objectives of study on a 470 samples. Findings revealed that participants who do physical activity for 3 days and accumulating at least 1500 metabolic equivalent tasks (MET) minutes per week or with combination of walking, moderate or vigorous intensity activities accumulating at least 3000 MET minutes were classified as highly active. Other participants were categorized as moderately active and low active/inactive. The results identified that lack of time due to busy lesson schedule was the most significant factors for not participating in physical activity among the samples. Priority on academic success over exercise was the most identified item that hinders individual to participate in physical activities. Thus, recommended the replication of this study to increase the generalizability of achieved results